Effect of glycine functionalization of 2D titanium carbide (MXene) on charge storage. Issue 11 (28th February 2018) - Chen, Chi; Boota, Muhammad; Urbankowski, Patrick; Anasori, Babak; Miao, Ling; Jiang, Jianjun; Gogotsi, Yury
Abstract : The expanded MXene by glycine functionalization exhibited an improved rate and cycling performance. Abstract : Restacking of two-dimensional (2D) flakes reduces the accessibility of electrolyte ions and is a problem in energy storage and other applications. Organic molecules can be used to prevent restacking and keep the interlayer space open. Here, we report on a combined theoretical and experimental investigation of the interaction between 2D titanium carbide (MXene), Ti3 C2 T x, and glycine. From first principle calculations, we presented the functionalization of glycine on the Ti3 C2 O2 surface, evidenced by the shared electrons between Ti and N atoms. To experimentally validate our predictions, we synthesized flexible freestanding films of Ti3 C2 T x /glycine hybrids. X-ray diffraction and X-ray photoelectron spectroscopy confirmed the increased interlayer spacing and possible Ti–N bonding, respectively, which agree with our theoretical predictions. The Ti3 C2 T x /glycine hybrid films exhibited an improved rate and cycling performances compared to pristine Ti3 C2 T x, possibly due to better charge percolation within expanded Ti3 C2 T x .